ANALISIS UPAYA UNTUK MENINGKATKAN DISIPLIN APARATUR SIPIL NEGARA DI PEMERINTAH KOTA SEMARANG - Patrick Satya Bareta (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
The purpose of this study is to analyze the condition of the discipline of State Civil Apparatus Discipline in the Semarang City Government. Analyze the regulations that have been implemented by the Semarang City Government in improving the discipline of state civil apparatus. Analyze efforts or strategies that can be done to improve the discipline of state civil apparatus. This study uses a qualitative approach with a case study method that focuses on efforts to improve the discipline of state civil apparatus (ASN) in the Semarang City Government through interviews, observation and documentation. In the interview, the selection of informants was carried out by purposive sampling. The data obtained were analyzed using the interactive analysis technique of the Miles and Huberman model which includes three main stages, namely data reduction, data presentation, and continuous drawing of conclusions to achieve validity and depth of information. The results of the ASN discipline research in the Semarang City Government continue to be pursued through the implementation of rules, supervision, and coaching. However, there are still obstacles such as delays, lack of responsibility, and low awareness of discipline, so that synergy is needed between leadership policies, reward and punishment systems, and increased work motivation. Semarang City Government Semarang City Government implements regulations such as PP No. 94 of 2021, electronic attendance, and technology-based performance monitoring. Regular evaluations of attendance and productivity are conducted to foster a professional, responsible, and service-oriented work culture. Efforts to improve civil servant discipline are carried out through consistent enforcement of regulations, fair rewards and punishments, quality leadership, and ongoing development. Utilizing technology and strengthening a professional work culture are key to realizing a civil servant with discipline and integrity in providing optimal service